Detection of child violence by nurses in child care consultation (Research, Society and Development, 2020)
The purpose of the juvenile phase is to make major changes in behavior. In this way it makes them more vulnerable to situations that compromise the integrity of their health and well-being. Nursing since its graduation must adapt to this reality and seek conditions to act safely and correctly, reassuring it. In view of the above, the objectives of this study are to understand through the bibliographic survey the knowledge of nurses about signs and symptoms of a child who suffered violence and to identify the actions taken by nurses in the face of child violence. The research was of bibliographic nature, carried through with the collection in virtual database. For this purpose, the Virtual Health Library (VHL) was used, in the following information base: Latin American and Caribbean Literature in Health Sciences (LILACS); Nursing Database (BDENF) and Online Medical Literature Search and Analysis System (MEDLINE) from February to March 2020. 15 articles were selected. It was analyzed that nurses identify and outline the care for children who are victims of violence, but greater coverage of the findings and safety is necessary for these professionals who make the complaints.